Orígenes, evolución y retos de la etnobiología boliviana - Victoria Reyes-García; Mónica Moraes R.; Álvaro Fernández-Llamazares; Narel Y. Paniagua-Zambrana (Revue d'ethnoécologie)
Ethnobiology is the study of the relationships that different societies establish with nature, through the anlysis of knowledge, uses and perceptions. Bolivia is a country with great biological and cultural diversity. In the last two decades, Bolivia has initiated a political process in view to defend indigenous identity and governance, which includes the revaluation of local ecological knowledge. This situation provides an excellent opportunity for the development and consolidation of ethnobiological research in the country. In this article, we document the biological and anthropological precursors of Bolivian ethnobiology and we analyze its evolution through three emblematic case studies: the first two show the confluence of a biological and an anthropological project towards ethnobiology, and the third one illustrates the benefits of the participatory approach. The last section addresses some of the major challenges posed by ethnobiology in Bolivia, focusing on four aspects that are necessary to lay a strong foundation for the development of the discipline: i) identification of documentary gaps and creation of a baseline; ii) methodological development with a focus on interdisciplinarity, iii) internationalization; and iv) generalization of participatory research, which helps initiate a dialogue between various types of knowledge. Ethnobiology can contribute to the resolution of contemporary environmental issues, but this potential cannot be realized without a greater inclusion of Indigenous Peoples and local communities.